Notary Responsibilities for the Occurrence of Identity Faketing In the Making of Authentic Deeds - Maudy Rahma Pranadia; Gunardi Lie (PT Publikasiku Academic Solution, 2023)
A notary is a public official who is appointed to make authentic deeds and has other authorities as referred to in Article 1 Number 1 Law Number 2 of 2014 on Amendment to Law Number 30 of 2004 on Office of Notary Public. If there is a negation or denial related to a deed drawn up by a Notary if the documents and/or information obtained regarding the drawing up of the deed turn out to be false, then it is the responsibility of the party who submitted the documents or provided the false identity. This is because the deed contains written statements from the appearers. there is no reason whatsoever for a Notary not to apply the precautionary principle in carrying out his or her position and must uphold the precautionary principle. This implies that all actions taken in the context of drawing up an authentic deed must be in accordance with the applicable laws and regulations so that they can be legally accounted for. In the drawing up of an authentic deed, the Notary must be responsible if the deed drawn up by him or she contains a mistake or an intentional violation by the Notary. Conversely, if the element of mistake or violation occurs from the appearing party, then as long as the Notary exercises his or her authority in accordance with the regulations, the relevant Notary cannot be held accountable because the Notary only records what was conveyed by the parties to be stated in the deed